Pemanfaatan Teknologi Informasi untuk Sistem Informasi Manajemen Sekolah: Studi Kasus pada SMA 78 Jakarta - Ayuliana, Ayuliana; Neva, Neva; Susanti, Novia; Fahreza, Fahreza (Bina Nusantara University, 2011)
Databases to manage data related to student and school are required to support the implemented information technology applications. This study aims to analyze and design a database system that supports the school management information systems, especially for SMA 78 Jakarta as a case study. Included in the system are the students and teachers data management, the management of school tuition, and the management of learning materials and assignments for students. This research uses data collection methods, with a literature study, questionnaires, interviews, observation, and studying the data obtained from the school. Analyses were performed on the results of questionnaires, interviews and observations to identify user needs. The design used conceptual and logical database system design. The result achieved is the application for school management information system that can be used by students, teachers and school officials in supporting learning process and school administration. The developed application is expected to be a medium for students and teachers to share information in teaching and learning activities and administrative processes.